The Analysis of Shouryakugo on Social Media Twitter - Sonda Sanjaya; Wistri Meisa; Hendityo Suryo Devanto (IZUMI, 2021)
This study examined the morphology of shouryakugo on social media Twitter. This study aims to determine the type and process of shouryakugo formation on Twitter. The study data were taken from tweets that were trending with hashtag # 社会 between January and March 2019. A descriptive qualitative design was employed in this study. The data obtained were categorized and analyzed based on the formation process. The results of this study showed the types and processes of shouryakugo formation. The findings include four forms of zenbu shouryakukei, 32 forms of gobu shouryakukei, five forms of chuushouryaku kei, one form of zengo shouryaku kei, and 21 forms of kousei youso tanbun ketsugoukei. Meanwhile, in the process of forming shouryaku, the researcher found four words with the omission of parts or all of the first words, two words with the omission of parts or all of the second words, twenty-five words with the omission of syllables at the end of words, two words with the omission of syllables at the end of the first word and all second words, twenty-one words with the omission of syllables at the end of the first word and the second-word element, three words with the omission of all second words, five words with the omission of middle words, one word with the omission of the first syllable of the first word and the final syllable of the second word.